2015
DOI: 10.1002/joc.4315
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the start, end, and length of frost‐free periods across the conterminous United States during the past century

Abstract: The timing of last spring frost dates (LSFDs), first fall frost dates (FFFDs), and frost-free period lengths (FFPLs) constrains freeze-thaw processes in hydrology, paces the annual life cycles of plants and animals, affects human food production, and influences land-atmosphere interactions, including the water and carbon cycles. Daily minimum temperature data for the conterminous United States (CONUS) from the Global Historical Climatology Network for the 1920-2012 period are used to determine LSFDs, FFFDs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
4
40
1
Order By: Relevance
“…3a and 3b, respectively) illustrate the CD plateau during the growing season. The duration of the frost-free season, our traditional measure of the climatological growing season, shows an area-average trend of +0.32 days/y (p < 0.05) over our study period that is consistent with previous fi ndings [Kunkel et al, 2004;Yu et al, 2014;McCabe et al, 2015]. The end of the CD plateau, our alternative measure to indicate the end of the growing season, showed an area-wide trend of +0.27 days/y (p < 0.05) over the 30-year study period that is consistent with autumn warming.…”
Section: Climatological Analysis Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3a and 3b, respectively) illustrate the CD plateau during the growing season. The duration of the frost-free season, our traditional measure of the climatological growing season, shows an area-average trend of +0.32 days/y (p < 0.05) over our study period that is consistent with previous fi ndings [Kunkel et al, 2004;Yu et al, 2014;McCabe et al, 2015]. The end of the CD plateau, our alternative measure to indicate the end of the growing season, showed an area-wide trend of +0.27 days/y (p < 0.05) over the 30-year study period that is consistent with autumn warming.…”
Section: Climatological Analysis Resultssupporting
confidence: 91%
“…The first is a traditional definition based on the last spring frost and first autumn frost dates (T min < 0°C) [e.g. McCabe et al, 2015]. Frost dates and the duration of the frost-free season are useful for assessing long-term seasonal changes as well as acute indicators of potential for vegetation freeze damage, especially in the transition from cold to warm seasons.…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…Even though the timing and duration of the frost-free season is important for natural and managed environments, including agricultural production and the phenologies of plant and animal species345, the relative importance of climatic factors that drive changes in components of the frost-free season over the past century is not well understood.…”
mentioning
confidence: 99%
“…Studies focused on regions of the western United States (U.S.) have reported correlations between frost timing and the Pacific-North American (PNA) pattern1617, which is characterized in its positive polarity by troughing over the eastern Pacific, ridging over the Rocky Mountains and troughing over eastern North America18. However, recent work extending frost-timing analysis to a century of data with coverage over the conterminous U.S. found statistically significant linkages to only the AMO5. The roles and relative importance of large-scale warming and dynamically induced atmospheric circulation effects in regulating observed variations in U.S. frost timing are thus not clear.…”
mentioning
confidence: 99%
“…Cutforth et al () concluded that the LFFS showed an increasing trend with the significant earlier LSFD and not significant later FFFD on the Canadian prairies during the latter half of the 20th century. McCabe et al () found that there were earlier LSFD, later FFFD, and longer LFFS for most locations across the conterminous United States during the past century. Although the trends of earlier LSFD, later FFFD, and longer LFFS were similar in different regions over the world, the magnitudes of trends among them were different.…”
Section: Introductionmentioning
confidence: 99%